The status of non - muslim married women and their right to maintenance / Fadzidah Hashim - Hashim, Fadzidah (Faculty of Law, 1984)
The aim of this paper is to study the status of women after they are married and in particular their rights to maintenance in Malaysia. With the enforcement of the Law Reform (Marriage and Divorce) Act 1976 on the 1st March 1982, various statutory provisions are laid down for their maintenance whereas previously one has mainly to resort to case law for guidance. This paper concerns solely with the non-muslim married women. Malaysia, in keeping with the trend going around the world, to review family law, has passed the Law Reform (Marriage and Divorce) Act 1976, which made great changes in the law pertaining to marriage and divorce. Under the Law Reform (Marriage and Divorce) Act 1976, polygamous marriage are prohibited thereby making it illegal for a man to take a second wife while the first marriage is in existence. The second wife will not be a wife in the eyes of law but a mistress and as such do not enjoy the rights conferred by law on the first wife like maintenance, division of joint property and many others. However if the marriage is contracted before the enforcement of the Law Reform (Marriage and Divorce) Act 1976, it will not affect the position of the second wife.